Two-Stage Hybrid Repair in a Patient with Acute Type A Aortic Dissection Associated with Right Aortic Arch with Aberrant Left Subclavian Artery Originating from a Kommerell Diverticulum - Doi, Toshio (Ann Vasc Dis, 2016)
Right aortic arch with aberrant left subclavian artery and Kommerell diverticulum are rare anomalies. A 42-year-old man was referred with sudden-onset chest pain. Enhanced computed tomography (CT) showed a right aortic arch with early thrombosed acute type A aortic dissection and an aberrant left subclavian artery arising from a Kommerell diverticulum. Medical therapy was instituted; however, follow-up CT revealed an ulcer-like projection. The patient was managed with a two-stage hybrid procedure comprising total arch replacement and endovascular repair and experienced no postoperative complications. Two-stage hybrid repair is a safe and effective surgical option for rare complex aortic anomalies.